Killer whales (Orcinus orca) in waters adjacent to the Chukotka Peninsula, Russia - Melnikov, Vladimir V.; Zagrebin, Igor A.; Zelensky, Gennadi M.; Ainana, Ludmilla I. (J. Cetacean Res. Manage., 2023)
Chukotkan hunters were employed as observers between 1990 and 2000 to document the occurrence of killer whales off the coast of the Chukotka Peninsula throughout the year. The study area was divided into three parts: the south, north and east coasts and all showed a significant negative correlation between sea-ice coverage and number of killer whales sighted (r =-0.76, -0.64 and -0.74 respectively). For all areas, the majority of whales were sighted during the summer months (June-September), but during years with late ice-destruction, whales arrived a month later than in ‘warm’ years. Killer whales were sighted three times as often per observation off the north coast than the east and twice as often when compared with the south coast and were also more likely to be part of a group off the north coast. The former was thought to be due to prey availability and the latter to increase the success of the hunt when targeting large prey species. Although the aim was not to determine abundance, a crude estimate of 56 was obtained, since this was the maximum number of killer whales ever reported independently on the same day. The data presented could be used to improve predictions of the most likely/unlikely times that killer whales are present off the Chukotka Peninsula, which would be beneficial to those conducting, for example, photoidentification surveys, or conversely seismic surveys.